The role of leptin, soluble leptin receptor, resistin, and insulin secretory dynamics in the pathogenesis of hypothalamic obesity in children - BEREKET, ABDULLAH; HAKLAR, GONCAGÜL; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (SPRINGER, 2009)
In this study, we have investigated the role of leptin, soluble leptin receptor(sOb-R), resistin, and insulin secretory dynamics in the development of hypothalamic obesity. Children who had hypothalamo-pituitary tumor were divided into two groups. First group included obese-overweight (hypothalamic obese = HOB group, n = 23) and second group included non-obese children (hypothalamic non-obese = HNOB group, n = 16). Exogenously obese-overweight children (OB group, n = 22) were included as controls. Basal and second-hour serum glucose and insulin in oral glucose tolerance test (OGTT), basal serum leptin, sOb-R, resistin levels, and homeostasis model assessment (HOMA) indexes were compared between the groups. Age, sex, and pubertal status were similar in study groups. Median and interquartile ranges of body mass index (BMI) z scores were similar in HOB and OB groups (2.0 (1.5-2.1) and 2.1 (1.8-2.3), respectively). Serum leptin levels corrected for BMI were highest and total leptin/sOb-R ratios (free leptin index (FLI)) tended to be higher in HOB than HNOB and OB groups, indicating leptin resistance (leptin/BMI, 4.0 (1.6-5.2), 1.5 (0.8-3.1), and 2.5 (1.8-3.5); FLI, 2.0 (0.8-3.5), 0.6 (0.3-1.2), and 1.5 (1-2.3) in HOB, HNOB, and OB groups; respectively). Serum resistin levels were similar in groups (2.6 (1.9-3.1), 2.8 (1.7-3.4), and 3.0 (2.2-3.5) ng/ml in HOB, HNOB, and OB groups, respectively). Basal serum glucose, basal and second-hour insulin levels in OGTT, and HOMA index were higher in OB group than the HOB and HNOB groups, indicating insulin resistance in simple obesity; however, increment of insulin to same glycemic load in OGTT was highest in the HOB group indicating insulin dysregulation (p < 0.05). Hypothalamic obesity seems to be related to both dysregulated afferent (leptin) and efferent (insulin) neural outputs through the autonomic nervous system resulting in energy storage as fat.
Keywords: Hypothalamic obesity; Leptin; Soluble insulin receptor; Resistin; Insulin; CHILDHOOD CRANIOPHARYNGIOMA; BINDING-ACTIVITY; GENETIC OBESITY; SERUM LEPTIN; ADIPONECTIN; GLUCOSE; ADOLESCENTS; DYSFUNCTION; BLOOD